Long-distance peptide signaling essential for nutrient homeostasis in plants. (December 2016) - Okamoto, Satoru; Tabata, Ryo; Matsubayashi, Yoshikatsu
Highlights: Several secreted peptides act as root-to-shoot long-distance mobile signals. Plants employ this long-distance signaling to adapt to fluctuating nutrient status. Transpiration may be a driving force for root-to-shoot translocation of peptides. Abstract : Organ-to-organ communication is indispensable for higher organisms to maintain homeostasis over their entire life. Recent findings have uncovered that plants, like animals, mediate organ-to-organ communication by long-distance signaling through the vascular system. In particular, xylem-mobile secreted peptides have attracted much attention as root-to-shoot long-distance signaling molecules in response to fluctuating environmental nutrient status. Several leguminous CLE peptides induced by rhizobial inoculation act as 'satiety' signals in long-distance negative feedback of nodule formation. By contrast, Arabidopsis CEP family peptides induced by local nitrogen (N)-starvation behave as systemic 'hunger' signals to promote compensatory N acquisition in other parts of the roots. Xylem sap peptidomics also implies the presence of still uncharacterized long-distance signaling peptides. This review highlights the current understanding of and new insights into the mechanisms and functions of root-to-shoot long-distance peptide signaling during environmental responses.